Norepinephrine versus Ephedrine to maintain arterial blood pressure during spinal anesthesia for cesarean section - Abdel-baset T. Ahmed (SVU - International Journal of Medical Sciences, 2022)
Background: Spinal anesthesia is recommended for elective cesarean sections, but maternal hypotension by may occur, resulting in severe maternal complications. To avoid spinal hypotension, many methods were attempted; fluid loading, vasopressors, or combination of both. Objectives: Our study aimed to compare administration of intermittent i.v. boluses of norepinephrine and ephedrine to guard against hypotensive effect of spinal anesthesia during delivery. Patients and methods: This study was conducted at Qena University Hospitals, sixty cases undergoing elective cesarean section under spinal anesthesia were enrolled. They were randomly allocated to two equal groups, group N received prophylactic i.v. bolus of norepinephrine 5 μg, group E received prophylactic bolus of i.v. ephedrine 10mg immediately after intrathecal block. Incidence of hypotension and the numbers of the boluses of vasopressors used were recorded and considered as primary outcomes, maternal complication during the surgery as secondary outcomes. Results: According to SBP, DBP, MAP there was significant lower values in groupE compared with group N. The mean number of boluses of vasopressors used during spinal anesthesia was significantly lower in Group N (2.2 vs. 5.8, P = 0.001). the mean number of hypotension episodes was also significantly lower in Group N (2.5 vs. 5.33, P = 0.001). Regarding operative maternal complications, Group N had a significantly lower nausea(16.7% vs. 66.7%, p=.001) vomiting (60% vs. 16.7%, p=0.001). shivering (23.3% vs. 0%, p=0.001). Conclusion: Norepinephrine can be used as an alternative vasopressor to maintain maternal blood pressure during spinal anesthesia for cesarean delivery, with lower incidence of maternal complication.